Al-DirÄsah al-MuqÄrinah Ê¿an KafÄ'ah al-Tarjamah al-Taá¸¥rÄ«riyyah min al-Lugah al-Ê¿Arabiyyah ilÄ al-Lughah al-IndÅ«nisiyyah wa Ê¿Aksuha - Jamilah, Mimi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The research is conducting the objectives of (1) knowing the written translation ability of Indo-Arabic Intensive Arabic students at the An-Nur Islamic Boarding School Surabaya and (2) knowing the written translation abilities of Indo-Arabic Intensive Arabic students at the An-Nur Islamic Boarding School Surabaya (3) knowing the comparison between Indo-Arabic and Indo-Arabic Written Translation for Arabic Language Intensive Students at the Annur Islamic Boarding School Surabaya. In this research, the writer uses a quantitative data analysis method using paired sample T-test with an SPSS application. In this case, to compare the variable (x) Arabic-Indo translation ability (y) Arabic-Indo written translation ability and the comparison between written Arabic-Indo and Indo-Arabic translations for Intensive Arabic Students at the An-Nur Islamic Boarding School Surabaya. The correlation between the Arabic-Indo and Indo-Arabic translations is 0.548, which means a strong relationship. T count > t table (4,402 > 2.002) implies that Ho is rejected and Ha is accepted, meaning that there is a significant comparison between the ability of written Arabic-Indo and Indo-Arabic translations of the Intensive Arabic students at the An-Nur Islamic boarding school in Surabaya.ØªÙ… Ø¥Ø¬Ø±Ø§Ø¡ Ø§Ù„Ø¨ØØ« Ø¨Ø£Ù‡Ø¯Ø§Ù: (1) Ù…Ø¹Ø±ÙØ© Ø§Ù„Ù‚Ø¯Ø±Ø© Ø¹Ù„Ù‰ Ø§Ù„ØªØ±Ø¬Ù…Ø© Ø§Ù„ÙƒØªØ§Ø¨ÙŠØ© Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ù„Ù…ÙƒØ«ÙØ© ÙÙŠ Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù†ÙˆØ± Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø¯Ø§Ø®Ù„ÙŠØ© Ø³ÙˆØ±Ø§Ø¨Ø§ÙŠØ§ (2) Ù…Ø¹Ø±ÙØ© Ù‚Ø¯Ø±Ø§Øª Ø§Ù„ØªØ±Ø¬Ù…Ø© Ø§Ù„ØªØØ±ÙŠØ±ÙŠØ© Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ù„Ù…ÙƒØ«ÙØ© ÙÙŠ Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù†ÙˆØ± Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø¯Ø§Ø®Ù„ÙŠØ© Ø³ÙˆØ±Ø§Ø¨Ø§ÙŠØ§ (3) Ù…Ø¹Ø±ÙØ© Ø§Ù„Ù…Ù‚Ø§Ø±Ù†Ø© Ø¨ÙŠÙ† Ø§Ù„ØªØ±Ø¬Ù…Ø© Ø§Ù„Ù…ÙƒØªÙˆØ¨Ø© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ù„Ù…ÙƒØ«ÙØ© ÙÙŠ Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù†ÙˆØ± Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø¯Ø§Ø®Ù„ÙŠØ© Ø³ÙˆØ±Ø§Ø¨Ø§ÙŠØ§.. ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« ØŒ ÙŠØ³ØªØ®Ø¯Ù… Ø§Ù„ÙƒØ§ØªØ¨ Ø·Ø±ÙŠÙ‚Ø© ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø§Ù„ÙƒÙ…ÙŠØ© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ø®ØªØ¨Ø§Ø± T Ù„Ù„Ø¹ÙŠÙ†Ø© Ø§Ù„Ù…Ù‚ØªØ±Ù†Ø© Ù…Ø¹ ØªØ·Ø¨ÙŠÙ‚ SPSS. ÙÙŠ Ù‡Ø°Ù‡ Ø§Ù„ØØ§Ù„Ø©ØŒ Ù„Ø¥ÙŠØ¬Ø§Ø¯ Ù…Ù‚Ø§Ø±Ù†Ø© Ø¨ÙŠÙ† Ø§Ù„Ù…ØªØºÙŠØ± (x) Ù‚Ø¯Ø±Ø© Ø§Ù„ØªØ±Ø¬Ù…Ø© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©-Ø§Ù„Ù‡Ù†Ø¯ÙŠØ© (y) Ø§Ù„Ù‚Ø¯Ø±Ø© Ø¹Ù„Ù‰ Ø§Ù„ØªØ±Ø¬Ù…Ø© Ø§Ù„Ù…ÙƒØªÙˆØ¨Ø© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©-Ø§Ù„Ù‡Ù†Ø¯ÙŠØ© ÙˆØ§Ù„Ù…Ù‚Ø§Ø±Ù†Ø© Ø¨ÙŠÙ† Ø§Ù„ØªØ±Ø¬Ù…Ø© Ø§Ù„Ù…ÙƒØªÙˆØ¨Ø© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©-Ø§Ù„Ù‡Ù†Ø¯ÙŠØ© ÙˆØ§Ù„Ù‡Ù†Ø¯ÙŠØ©-Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ù„Ù…ÙƒØ«ÙÙŠÙ† ÙÙŠ Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù†ÙˆØ± Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø¯Ø§Ø®Ù„ÙŠØ© Ø³ÙˆØ±Ø§Ø¨Ø§ÙŠØ§. Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø¹Ù„Ø§Ù‚Ø© Ø¨ÙŠÙ† Ø§Ù„ØªØ±Ø¬Ù…ØªÙŠÙ† Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ø§Ù„Ø¥Ù†Ø¯ÙˆÙ†ÙŠÙ‰ÙŠØ© ÙˆØ§Ù„Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù‡ÙŠ 0.548 ØŒ Ù…Ù…Ø§ ÙŠØ¹Ù†ÙŠ Ø£Ù† Ù‡Ù†Ø§Ùƒ Ø¹Ù„Ø§Ù‚Ø© Ù‚ÙˆÙŠØ© ØŒ Ùˆ t Ø¹Ø¯ > Ø¬Ø¯ÙˆÙ„ t (4,402 > 2.002) ØŒ Ù…Ù…Ø§ ÙŠØ¹Ù†ÙŠ Ø£Ù† Ho Ù…Ø±ÙÙˆØ¶ Ùˆ Ha Ù…Ù‚Ø¨ÙˆÙ„ ØŒ Ù…Ù…Ø§ ÙŠØ¹Ù†ÙŠ Ø£Ù† Ù‡Ù†Ø§Ùƒ Ù…Ù‚Ø§Ø±Ù†Ø© ÙƒØ¨ÙŠØ±Ø© Ø¨ÙŠÙ† Ù‚Ø¯Ø±Ø© Ø§Ù„ØªØ±Ø¬Ù…Ø§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ù„Ù‡Ù†Ø¯ÙŠØ© Ø§Ù„Ù…ÙƒØªÙˆØ¨Ø© ÙˆØ§Ù„Ù‡Ù†Ø¯ÙŠØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©. Ø·Ù„Ø§Ø¨ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ù„Ù…ÙƒØ«ÙÙˆÙ† ÙÙŠ Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù†ÙˆØ± Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø¯Ø§Ø®Ù„ÙŠØ© ÙÙŠ Ø³ÙˆØ±Ø§Ø¨Ø§ÙŠØ§.